Deepening structural reform in Africa : lessons from East Asia - Wallace, Laura; International Monetary Fund.; Japan; World Bank. (Washington, D.C. : International Monetary Fund, 1997)
The papers and proceedings of a seminar held in Paris in May 1996 on "Deepening Structural Reforms and Policies for Growth in Africa" are covered in this volume.
"Proceedings of a seminar held in Paris, May 13-14, International Monetary Fund, Ministry of Finance of Japan."
Includes bibliographical references.
oif 29/10/15
Loan
Keywords: Africa, Sub-Saharan -- Economic policy -- Congresses; Africa, Sub-Saharan -- Economic conditions -- 1960- -- Congresses; East Asia -- Economic policy -- Congresses; East Asia -- Economic conditions -- Congresses